Distribución diamétrica y stock de carbono de las especies arbóreas en la parcela V del Arboretum “el huayo”, Puerto Almendra, Loreto, 2022 - Novoa Vásquez, Annie Johana (2023)
Tree species suffer changes in diameter, height and the way they store carbon, this in turn is the consequence of climate change and its sudden alteration in the atmosphere. The study determined the diameter distribution and carbon stock of tree species in plot V of the “El Huayo” Arboretum, Puerto Almendra, whose study area belongs to the mid-terrace forest. It was possible to determine 718 tree individuals, with 145 species and 36 families, of which the most representative species is Alchornea triplinervia (Spreng.) Müll. Arg (11.70%) with 52.50 trees/ha and Caryocar glabrum (4.74%) with 21.25 trees/ha. The tree species with the greatest presence are distributed in diameter class between 10 to 19,999 cm (237.50 trees/ha) and between 20 to 29,999 cm (120 trees/ha). The aerial biomass contains a total of 191.55 t/ha, but of the 15 representative species it has 118.57 t/ha, and the largest biomass is distributed in a diameter class of 20-19.999 cm (45.48 t/ha), followed, between 30 to 39.999 cm (44.11 t/ha), and a total carbon stock of 153.24 tC and 95.78 tC/ha of the studied area, distributed in diameter class between 20 and 19.999 cm (22.74tC /ha) and between 30 to 39,999 cm (22.05 tC/ha), and Alchornea triplinervia (Spreng.) Müll. It has the highest aerial biomass content with 50.88 t and 31.80 t/ha and the carbon stock of 25.44 tC and 15.90 tC/ha, therefore, the hypothesis test using non-parametric statistics, The Spearman correlation indicates that there is a 95% association between the diameter distribution and the carbon stock stored in the evaluated forest, at a significance level of ?= 0.05.